2011
DOI: 10.1002/arch.20427
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and immunolocalization of odorant binding protein 1 in the lucerne plant bug, Adelphocoris lineolatus (GOEZE)

Abstract: In the insect phylum, the relationships between individuals and their environment are often modulated by chemical communication. Odorant binding proteins (OBPs) are widely and robustly expressed in insect olfactory organs and play a key role in chemosensing and transporting hydrophobic odorants across the sensillum lymph to the olfactory receptor neuron. In this study, a novel OBP gene (AlinOBP1) in the lucerne plant bug, Adelphocoris lineolatus was identified, cloned and expressed. Real-time PCR results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 50 publications
3
66
0
Order By: Relevance
“…In the Lucerne plant bug, Adelphocoris lineolatus , expression of OBP1 is 1.91 times higher in male than in female antennae and this protein was shown to exhibit high binding affinity with two putative pheromone components (Gu et al, 2011b). Recent study suggested that OBP expression could be regulated by nutritional state.…”
Section: Discussionmentioning
confidence: 99%
“…In the Lucerne plant bug, Adelphocoris lineolatus , expression of OBP1 is 1.91 times higher in male than in female antennae and this protein was shown to exhibit high binding affinity with two putative pheromone components (Gu et al, 2011b). Recent study suggested that OBP expression could be regulated by nutritional state.…”
Section: Discussionmentioning
confidence: 99%
“…Using the OBP sequence motif search [23], [26], [33], [39], homology searching [25], [41], [38], [42] and genomic sequence analyses [35], [30] we have annotated 90 genes encoding putative OBPs in N. vitripennis . This is the largest OBP gene family so far reported in insects and has allowed us to identify some of unique features and to be able to study evolution origin of these features.…”
Section: Discussionmentioning
confidence: 99%
“…This plant bug and several other mirids are extremely herbivores and cause severe damage to many important crops such as beans, strawberries, peaches, cotton, and various seed crops each year [3][5]. These mirids are attracted to flowering plants especially cotton, alfalfa and mung bean [3], [4], [6][9], suggesting mirids use chemical information from these flowers to forage suitable hosts and find oviposition sites. Identification of attractant molecules and their interactions with olfactory proteins are meaningful for monitoring and mass-trapping these mirids and other insect pest [10], [11].…”
Section: Introductionmentioning
confidence: 99%